Study of Dynamic Properties in MgSiO3 Liquid under Compression by Mean of Molecular Dynamics Simulation - Kien, Pham Huu; Tuyen, Ho; Trang, Giap Thi Thuy (VNU Journal of Science: Mathematics - Physics, 2022)
In this paper, the dynamic properties in MgSiO 3 liquid are investigated by mean of molecular dynamics (MD) simulation. Our model informed that the total radial distribution function is good agreement experiment and other simulation data. We found that the SiO x -SiO x’ and MgO y -MgO y’ linked pairs have a tendency to forming clusters with the structural heterogeneity. The dynamic properties in models have been investigated though the self-diffusion and electrical conductivity. Moreover, we have presented evidence about the relationship between structure and dynamic heterogeneity in the model.